Model Pembelajaran Discovery Learning dalam Meningkatkan Hasil Belajar Peserta Didik Pasca Pandemi Covid-19 - Laeny Siti Hasanah (Jurnal TEDC, 2023)
This study aims to determine the increase in learning outcomes through the Discovery Learning learning model as a learning innovation that can be applied by educators after the Covid-19 pandemic. Through literature review, the "library research" method of literature analysis was used in this study to complete the analysis of the various sources used. The formulation of research questions at the beginning of the study was followed by a review of research findings related to tracing past journals using indexed journal articles, books, theses, and online articles related to the application of Discovery Learning to collect data for this literature review. The results of the literature study show that after the Covid-19 pandemic that occurred in Indonesia, the application of teaching and learning strategies using the Discovery Learning model was quite successful in increasing student learning outcomes. From the literature studies that have been conducted, it is revealed that Discovery Learning as a post-Covid-19 learning model contributes to improving the final learning outcomes and teaching processes of students.